2004
DOI: 10.1590/s1679-62252004000100001
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of the genus Hemiancistrus Bleeker (Teleostei: Siluriformes: Loricariidae) from the upper rio Uruguai basin

Abstract: Two new species of Hemiancistrus are described: Hemiancistrus votouro n. sp. and Hemiancistrus meizospilos n. sp. from upper rio Uruguai basin. They differ from their congeners except H. chlorostictus, H. megacephalus, and H. macrops by the presence of light dots on fins and lateral and dorsal portions of head and body. Hemiancistrus votouro and H. meizospilos differ from the species above by meristic and morphometric data and by the color pattern.
Duas novas espécies de Hemiancistrus são descritas: Hemianc…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 2 publications
(1 reference statement)
0
18
0
8
Order By: Relevance
“…Remarks: Type locality interpreted by Isbrücker (1992b) (Cardoso & Lucinda, 2003). Hemiancistrus spinosissimus Cardoso & Lucinda, 2003 Hemiancistrus spinosissimus Cardoso & Lucinda, 2003: 79, fig.…”
Section: Hemiancistrus Bleeker 1862mentioning
confidence: 99%
See 2 more Smart Citations
“…Remarks: Type locality interpreted by Isbrücker (1992b) (Cardoso & Lucinda, 2003). Hemiancistrus spinosissimus Cardoso & Lucinda, 2003 Hemiancistrus spinosissimus Cardoso & Lucinda, 2003: 79, fig.…”
Section: Hemiancistrus Bleeker 1862mentioning
confidence: 99%
“…Hemiancistrus spinosissimus Cardoso & Lucinda, 2003 Hemiancistrus spinosissimus Cardoso & Lucinda, 2003: 79, fig. 4 (lower (Cardoso & Pezzi da Silva, 2004).…”
Section: Hemiancistrus Bleeker 1862mentioning
confidence: 99%
See 1 more Smart Citation
“…This large diversity has resulted in problems of species identification and many new species have been continuously described (Pereira and Oyakawa, 2003;Cardoso and Silva, 2004). Traditionally, Loricariidae has been divided in six subfamilies: Hypostominae, Ancistrinae, Loricariinae, Hypoptopomatinae, Neoplecostominae and Lithogeninae (Reis, Kullander and Ferraris Jr, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Although some authors reported the presence of Bryconops species in the rio Tocantins (e.g., Lucinda et al, 2007;Lima & Caires 2011), Bryconops tocantinensis is the first species of Bryconops described from the rio Tocantins drainage and may be an additional example of exclusive fish species from its upper and middle portion, which is recognized by several authors as an area of endemism for several Neotropical freshwater fish groups (e.g., Cardoso & Lucinda, 2003;Bertaco & Carvalho, 2010;Bertaco et al, 2011aBertaco et al, , 2011b …”
Section: Discussionmentioning
confidence: 99%